Physical Mechanical Properties of Biodegradable Plastics from Cassava Starch with Variation of Bagasse and Glycerol. - Triana Lindriati; Andrew Setiawan Rusdianto; Bustani Pakartiko; Firda Ainia Adha (Journal La Lifesci, 2021)
Environmental problems are related to plastic waste that difficult to degrade naturally. Polysaccharides in the form of gelatinized cassava starch and bagasse containing 52.70% cellulose can replace commercial plastic polymers. This research was aimed to determine the effect of variations in bagasse and glycerol on physical, mechanical and biodegradation tests. The study used 2 factors CRD consisting of the addition of bagasse and glycerol. The results showed that the addition of bagasse and glycerol reducing the brightness with a value range of 44.82-76.15 and increased absorption between 2.61-10.64%. The thickness occurred between 0.79-1.11mm. The tensile strength values are 8.30-14.33 MPa, inversely proportional to the elongation value between 11.85-94.22%, but directly proportional to the modulus young value between 0.09-1.24 MPa. The highest biodegradation values were 0% bagasse and 40% glycerol. The three best treatments were found in the combination treatment of bagasse and glycerol 0% 20%, 0% 30%, and 0% 40%.